Grandma tells a story - Grambling, Lois G.; Willingham, Fred (Watertown, MA : Whispering Coyote, 2002)
A grandmother and grandfather eagerly anticipate the birth of their first grandchild.
3.2
K-3
K-3
School Library Journal
Keywords: Grandparents -- Fiction; Birth -- Fiction; Babies -- Fiction; Grandparents -- Fiction; Childbirth -- Fiction; Infants -- Fiction